Comparative Studies on Homemade Bread Produced from Blends of Wheat Flour with Each of Cassava, Maize and Whole Wheat Flour - , E. O. Esho; , A. T. Cole; , F. O. Ojo; , I. D. Ajewole (Archives of Current Research International, 2018)
Homemade bread produced from blends of wheat flour with cassava flour (WCF), wheat flour with maize flour (WMF), and wheat flour with whole wheat flour (WWF) at varying proportions were compared. The bread samples were analysed for sensory evaluation, nutritional value and presence of microorganisms. Sensory evaluation assessment was based on bread’s appearance, taste, texture and odour. Proximate and mineral analyses were done using laboratory protocols described by AOAC. Pour plate technique was used to estimate the microbial population and isolates were identified using laboratory procedures. WCF, WMF and WWF blends at ratio 9:1 has the highest acceptability. The percentage of crude protein for the three flour-blends ranges from 12.61 to 27.41 %, 0.31 to 0.70 % for crude fibre, 11.91 to 16.91 % for fat, 0.10 to 0.13 % for ash, 22.25 to 24.91 % for moisture content, 32.85 to 52.82 % for carbohydrate, 115 to 121.68 mg/100g for K, 95.61 to 107.45 mg/100g for Ca, 92.50 to 96.50 mg/100g for P, 21.65 to 27.91 mg/100g for Mg, 3.75 to 5.20 mg/100g for Fe and 527.20 to 552.40 mg/100g for Na. Estimated bacterial population varies from 0.68 × 106 to 5.81× 107 cfu/g and 1.04× 107 to 2.50× 108 cfu/g for fungal population. Two Bacillus sp. were bacterial isolates recovered from the bread samples while Mucor sp., Aspergillus flavus, Aspergillus tamarii, Neurospora sp., Penicillium chrysogenum, Fusarium compacticum and Rhizopus sp. were fungi isolated. Bread samples made from each of the composite flour at ratio 9:1 were at their best with WMF blend being the overall best.